Heterogeneity and cooperation youth and social engagement in the Philippines - Co, Edna E. A.; Neame, Arthur (2000)
Heterogeneity is a possible social accord among development players only when they reckon when differences in views, approaches, resources and interests. However, bringing together the differing social player requires managerial skills and a smartness to apply these skills in a political context. The multi-sectoral program on the out-of-school children an youth (OSCY) is an off shoot of the trailblazing efforts of the International Youth Foundation (IYF) and the World Bank (WB) under the latter's Business as Partners for Development" brainchild. A salient feature of the program is the engagement of government and non-government, the business sector as well as corporate foundations, in the enhancement of economic vestibules for the out-of-school youth (OSY).
Keywords: School dropouts; Out-of-School Youth; International Youth Foundation (IYF); Kabataan (Youth) 2000; National Youth Commission; Corporate governance; Bureau of Non-Formal Education (BNFE)